TINDAK TUTUR PRAMUSAJI RESTORAN DI MASA PANDEMI COVID-19 - Kadek Ayu Ekasani; Ida Ayu Gayatri Kesumayathi; Putu Dian Yuliani Paramita (Widyadari : Jurnal Pendidikan, 2021)
This study aims to analyze the speech acts of restaurant waiters during the COVID-19 pandemic. This research is a follow-up to illocutionary speech acts that are used by waiters in their activities to serve food and drinks is considered very important to do. The theory used was Searle's illocutionary speech act theory. The data were collected using observation, interview, and note-taking methods and then described qualitatively. The results of this study indicated that there were 4 categories of illocutionary speech acts, namely assertive (reporting, reporting); directive (ordering, requesting, asking, examining, and asking permission); commissive (expectation); and expressive (thanks, greetings and congratulations). Meanwhile, the new speech uttered by the waiter during the pandemic was included in the directive speech act.